2006
DOI: 10.1111/j.1468-5957.2006.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long Run Share Price Performance of Malaysian Initial Public Offerings (IPOs)

Abstract: This paper investigates the long run share price performance of 454 Malaysian IPOs during the period 1990 to 2000. In contrast with developed markets, significant over performance is found for equally-weighted event time CARs and buy-and-hold returns using two market benchmarks, though not for value-weighted returns or using a matched company benchmark. The significant abnormal performance also disappears under the calendar-time approach using the Fama-French (1993) three factor model. While the long run perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 51 publications
(128 reference statements)
9
33
1
Order By: Relevance
“…They reported that regarding the economic assumption of a downward sloping demand for shares, that the increase in the share retention percentage by the pre-IPO owners has led to a decrease in the number of available shares for trading, which causes investors to treat the available shares as a scarce commodity,which could lead to an increase in share prices. In the Malaysian IPO market, Ahmad-Zaluki, Campbell and Goodacre (2007) reported an average retention ratio of 76.6% in the whole IPO market, 75.9% in the Main Board, and 77.0% in the Second Board. According to the previous arguments, the current study supports three hypotheses, which are H1, H4 and H5.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that regarding the economic assumption of a downward sloping demand for shares, that the increase in the share retention percentage by the pre-IPO owners has led to a decrease in the number of available shares for trading, which causes investors to treat the available shares as a scarce commodity,which could lead to an increase in share prices. In the Malaysian IPO market, Ahmad-Zaluki, Campbell and Goodacre (2007) reported an average retention ratio of 76.6% in the whole IPO market, 75.9% in the Main Board, and 77.0% in the Second Board. According to the previous arguments, the current study supports three hypotheses, which are H1, H4 and H5.…”
Section: Resultsmentioning
confidence: 99%
“…There are several methodologies that could be used to calculate the aftermarket performance of IPOs, and there is no consensus on which of them provides better results. 3 Therefore, we think that it is better to combine several measures as it is specified that results are very sensitive to the chosen performance measure (Ahmad-Zaluki et al, 2007;Purnanadam and Swaminathan, 2004…).…”
Section: Variables Measures and Methodologymentioning
confidence: 99%
“…However, the Malaysian IPO market recorded a significant overperformance of 18.20 percent. Recently, Ahmad-Zaluki et al (2007) also established a positive performance on the Malaysian stock market over the period 1990-2000, when they compiled an equally-weighted portfolio. However, they provide additional results regarding the value-weighted abnormal returns that are on average statistically negative.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mixed findings have been documented for long-run IPO performance, with on the one hand, findings of underperformance reported in the developed countries, like the US and UK (Espenlaub, Gregory, & Tonks, 2000;Gompers & Lerner, 2003;T. Loughran & Ritter, 1995); Ritter (1991); and, on the other hand, evidences of overperformance in the developing countries like Malaysia, Singapore and Turkey (Ahmad-Zaluki, Campbell, & Goodacre, 2007;Banu Durukan, 2002;P. Lee, S. Taylor, & T. Walter, 1996b).…”
Section: Introductionmentioning
confidence: 98%